Transport of ixodid ticks and tick-borne pathogens by migratory birds - Hasle, Gunnar (Frontiers in Cellular and Infection Microbiology, 2013)
Birds, particularly passerines, can be parasitized by Ixodid ticks, which may be infected with tick-borne pathogens, like Borrelia spp., Babesia spp., Anaplasma, Rickettsia/Coxiella, and tick-borne encephalitis virus. The prevalence of ticks on birds varies over years, season, locality and different bird species. The prevalence of ticks on different species depends mainly on the degree of feeding on the ground. In Europe, the Turdus spp., especially the blackbird, Turdus merula, appears to be most important for harboring ticks. Birds can easily cross barriers, like fences, mountains, glaciers, desserts and oceans, which would stop mammals, and they can move much faster than the wingless hosts. Birds can potentially transport tick-borne pathogens by transporting infected ticks, by being infected with tick-borne pathogens and transmit the pathogens to the ticks, and possibly act as hosts for transfer of pathogens between ticks through co-feeding. Knowledge of the bird migration routes and of the spatial distribution of tick species and tick-borne pathogens is crucial for understanding the possible impact of birds as spreaders of ticks and tick-borne pathogens. Successful colonization of new tick species or introduction of new tick-borne pathogens will depend on suitable climate, vegetation and hosts. Although it has never been demonstrated that a new tick species, or a new tick pathogen, actually has been established in a new locality after being seeded there by birds, evidence strongly suggests that this could occur.